Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 77. Beitrag. Coleoptera: Scarabaeidae II (Glaphyrinae, Sericinae, Melolonthinae, Rutelinae, Hopliinae, Cetoniinae, nebst Nachträgen zu Trichiinae und Valginae). - Petrovitz, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1969)
This second partial study of the Scarabaeidae covers the subfamilies Glaphyrinae, Sericinae, Melolonthinae, Rutelinae, Hopliinae, Cetoniinae. The evaluation is based on the material collected by the expedition to Albania by Deutsches Entomologisches Institut, 917 individuals of 28 species, and on 502 individuals from Deutsches Entomologisches Institut, the Museum of Natural History in Vienna, the Zoological Museum in Berlin and from the author’s collection, a total of 1419 individuals of 50 species. Publications record 14 other species from Albania (which are included only in the table of distribution). Thus a total of 64 species of these 6 subfamilies could be registered, not counting some forms. The table of distribution permits a comparison with the research on the adjacent regions. The first partial study of the Scarabaeidae by J. Schulze (1963) is supplemented by material for the subfamilies Trichiinae (53 individuals of 3 species) and Valginae (5 individuals of 1 species). Of the 162 species of Scarabaeidae on the Balkan peninsula, the two partial studies record 74 from Albania: 4 Dynastinae, 1 Valginae, 5 Trichiinae, 3 Glaphyrinae, 9 Sericinae, 17 Melolonthinae, 16 Rutelinae, 8 Hopliinae, 11 Cetoniinae.